OPERATION AND MAINTENANCE CHILLER TIPE SCREW PADA GEDUNG PLAZA PT. XYZ - Bintang Ramadhan Hermnato; Gabriel Xaverius Englando Rajagukguk; Agung Rizky; Ferly Fikri Ramadhan; Fajar Paundra (ELEMEN : JURNAL TEKNIK MESIN, 2026)
This report discusses the operational and maintenance processes of a screw-type chiller at Plaza PT XYZ. Chiller systems are crucial for maintaining the temperature in multi-story buildings, especially in tropical countries like Indonesia. The methods used in data collection include direct observation, interviews, and literature research on cooling systems were conducted during the practical work. While modular chillers are used outside working hours to save energy, screw chillers were chosen for their efficiency and high cooling capacity. The primary focus in maintaining system performance is regular maintenance, including preventive and corrective measures. These activities enhance understanding of the application of Heating, Ventilation, and Air Conditioning (HVAC) systems in the business world and highlight the importance of proper maintenance management to ensure buildings operate comfortably and efficiently.